Some Aspects of Counsellor Education in Canada with Emphasis on Career Development - Hassard, J. Harvey (Canadian Journal of Counselling and Psychotherapy, 2012)
The present study was initiated to examine some of the practices of graduate preparation of counsellors in Canadian universities. The intent was to provide data concerning a range of activities in this fieldwith some emphasis upon career development. Faculty members of faculties of education responsible for the preparation of counsellors were interviewed. Information was obtained on the experiential background of counsellor educators, the theoretical orientations employed, the programs, career development courses, the theories of career development in terms of popularity, the skills needed in the training of counsellors, standardized tests used in career development, recent changes in the programs, the impor- tant components of counsellor education in career development, the importance of areas of career development in counsellor education, the kinds of decision-making strategies em- ployed, changes in research in career development, the counsellor's changing roles, and future views of career counselling.